The Implementation of Constructivism-Based Student Worksheets within The Theme ‘The Prevention of Land and Forest Fire’ in Science Education for Grade VII of Secondary Schools in Riau - Yustina, Y.; Kapsin, K. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2017)
The issues of land and forest fire require a comprehensive effort, one of which is through the dissemination of educational values, such as science education. This verification study aims to examine the truth of the stage competence on the constructivism approach of the advanced test on student woksheet 1 and 2 and compare it with the test results 2 on the theme of forest and land fire and peat swamp ecosystem as well as global warming and its impact. The study was conducted in the laboratory of Biology department, Faculty of Teacher Training and Education, Universitas Riau and SMPN 1 Bungaraya in September-December 2016. This type of research is verivication research of advanced test results with test results on 2 sets of developed student worksheet. The data were collected from student worksheet. The results from this study indicate that students’ competence in constructing ideas through constructivism approach is ‘good’ at student worksheet 1 (mean score=3.27) and ‘very good’ at student worksheet 2 (mean score=3.43). The data also show that there was a consistency between the advanced test to the experimental test II. This study concludes that student worksheet 1 and student worksheet 2 can improve the students’ competence in building their knowledge on the topic of forest and land fires, and both worksheets (student worksheet 1 and 2) are eligible to be used as a reference for teaching science subject for Grade VII.